Variational approach for 𝜓-Hilfer fractional operator - Sousa, José Vanterler da Costa (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2022)
In this work, we aim to present properties that characterize a variational structure in the 𝜓-fractional space Hp𝛼,𝛽;𝜓(Ω) for the 𝜓-Hilfer fractional operator. The importance of these results are strongly used in the investigation of fractional differential equations involving problems such as: 𝑝-Laplacian, concaveconvex, singular double phases, among others.